Mechanisms of charge transfer in human copper ATPases ATP7A and ATP7B. Issue 4 (5th February 2017) - Tadini‐Buoninsegni, Francesco; Smeazzetto, Serena
Abstract: ATP7A and ATP7B are Cu + ‐transporting ATPases of subclass IB and play a fundamental role in intracellular copper homeostasis. ATP7A/B transfer Cu + ions across the membrane from delivery to acceptor proteins without establishing a free Cu + gradient. Transfer of copper across the membrane is coupled to ATP hydrolysis. Current measurements on solid supported membranes (SSM) were performed to investigate the mechanism of copper‐related charge transfer across ATP7A and ATP7B. SSM measurements demonstrated that electrogenic copper displacement occurs within ATP7A/B following addition of ATP and formation of the phosphorylated intermediate. Comparison of the time constants for cation displacement in ATP7A/B and sarcoplasmic reticulum Ca 2+ ‐ATPase is consistent with the slower phosphoenzyme formation in copper ATPases. Moreover, ATP‐dependent copper transfer in ATP7A/B is not affected by varying the pH, suggesting that net proton counter‐transport may not occur in copper ATPases. Platinum anticancer drugs activate ATP7A/B and are subjected to ATP‐dependent vectorial displacement with a mechanism analogous to that of copper. © 2016 IUBMB Life, 69(4):218–225, 2017